Neonatal Simulation Program: A 5 Years Educational Journey From Qatar - Bayoumi, Mohammad A. A.; Elmalik, Einas E.; Ali, Hossamaldein; D'Souza, Sunitha; Furigay, Jojo; Romo, Ava; Shyam, Sunitha; Singh, Rajvir; Koobar, Olfa; Al Shouli, Jihad; van Rens, Matheus; Abounahia, Fouad F.; et al. (Frontiers in Pediatrics, 2022)
We describe the process of implementation, adaptation, expansion and some related clinical intuitional impacts of the neonatal simulation program since its launch in 2016 in a non-simulation neonatal unit. The team has developed 6 types of curricula: 1 full-day course and 5 half-day workshops. A total of 35 free of charge simulation courses/workshops were conducted, 32 in Qatar and 3 abroad with a total of 799 diverse participants. There was a steady increase in the overall success rate of PICC insertion from 81.7% (309/378) to 97.6% (439/450) across 3 years (P <0.0001). The first attempt PICC insertion success rate has been also increased from 57.7% (218/378) to 66.9% (301/450) across 3 years. The mean duration of PICC insertion has been improved from 39.7±25 minutes to 34.9±12.4 minutes after implementing the program (P= 0.33). The mean duration of the LISA catheter insertion at the beginning of the workshop was 23.5±15.9 seconds compared to 12.1±8.5 seconds at the end of the workshop (P = 0.001). When it came to clinical practice in real patients by the same participants, the overall LISA catheter insertion success rate was 100% and the first attempt success rate was 80.4%. The mean duration of LISA catheter insertion in real patients was 26.9±13.9 seconds compared to the end of the workshop (P = 0.001). The mean duration of the endotracheal intubation at the beginning of the workshop was 12.5±9.2 seconds compared to 4.2±3.8 seconds at the end of the workshop (P = 0.001). In real patients, the first-attempt intubation success rate has been improved from 37/139 (26.6%) in the first year to 141/187 (75.5%) in the second year after the program implementation (P = 0.001). The mean duration of successful endotracheal intubation attempts has been improved from 39.1±52.4 seconds to 20.1±9.9 seconds (P = 0.78). As per the participants, the skills learned in the program sessions help in protecting neonates from potential harm and improve the overall neonatal outcome. Implementing a neonatal simulation program is a promising and feasible idea. Our experience can be generalized and replicated in other neonatal care institutions.